Patient-specific modelling of pulmonary arterial hypertension: wall shear stress correlates with disease severity - C. H. Armour; C. H. Armour; D. Gopalan; B. Statton; D. P. O’Regan; L. Howard; M. R. Wilkins; X. Y. Xu; A. Lawrie (Frontiers in Bioengineering and Biotechnology)
IntroductionPulmonary arterial hypertension (PAH) requires an invasive right heart catheter (RHC) procedure for diagnosis. Patients can present with initial symptoms and interact with healthcare institutes for up to 3 years before referral for diagnosis. Thus, there is a great need to develop non-invasive tools, to better screen patients and improve early diagnosis rates.Methodsseven patients diagnosed and treated for PAH were included in this study. Patient-specific computational fluid dynamics (CFD) models were built for all patients, with all model parameters tuned using non-invasive imaging data, including CT, cardiac MR, echocardiogram, and 4D-flow MRI scans–crucially, a 3D inlet velocity profile was derived from 4D-flow MRI.ResultsCFD models were quantitatively and qualitatively well matched with in-vivo 4D-flow hemodynamics. A linear correlation of R2 = 0.84 was found between CFD derived time-averaged wall shear stress (TAWSS) and RHC measured mean pulmonary pressure (key diagnostic value): low TAWSS correlated with high pressure.ConclusionThis study highlights TAWSS as a potential computational biomarker for PAH. The clinical use of TAWSS to diagnose and stratify PAH patients has the potential to greatly improve patient outcomes. Further work is ongoing to validate these findings in larger cohorts.